STUDY OF INTERACTION BETWEEN PURIFIED HYPERICIN PREPARATIONS AND DNA (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
Isolation and fractionation of total methanol extract, obtained from Hypericum perforatum L. flowers, using the method of gel-chromatography on columns, containing sephadex LH-20, were performed. Absorption and fluorescent spectroscopy, as well as the method of TLC have shown the high purity of obtained hypericin preparations. Interaction between hypericin and DNA was investigated. It was shown that hypericin interacts with purine and pyrimidine sequences of DNA selectively and in different ways.
Keywords: methanol extract; $Crocus~sativus$ L.; gel-chromatography; hypericin